Associations of baseline depressed mood and happiness with subsequent well-being in cardiac patients. (February 2017) - Craner, Julia; Douglas, Kristin Vickers; Dierkhising, Ross; Hathaway, Julie; Goel, Kashish; Thomas, Randal J.
Abstract: Rationale: The relationship between depressive symptoms and adverse outcomes for patients with cardiac problems has been well established for several decades. However, less is known about other factors that may influence psychosocial outcomes for cardiac patients. Objective: To evaluate the association between baseline happiness and depressed mood on later psychosocial functioning among cardiac patients. Method: Participants ( N  = 250) were patients who had received medical treatment at an academic medical center for a cardiac event. Participants completed questionnaires at two time points: Approximately 2 weeks after they had been discharged from the hospital (baseline) and again 12 weeks later. Participants completed validated measures of depressed mood, happiness, health distress, expectations about health, and quality of life. Results: Baseline depressed mood and happiness both significantly predicted health-related distress and depressive symptoms at follow up. Happiness ratings were associated with lower distress and depressed mood, whereas scores for depressive symptoms showed the opposite pattern. Happiness, but not depressed mood, was a significant predictor of more positive quality of life ratings. Conversely, only depressed mood was a significant predictor of less positive expectations about health. Conclusion: The results of this study suggest that investigating positive baseline affect in addition to depressed mood provides additional useful information that may help explain why some patients have more negative outcomes following cardiac events. Highlights: Happiness and depressed mood predict psychosocial outcomes in cardiac patients. Baseline happiness and depressed mood were associated with well-being at 12 weeks. Depressed mood and happiness uniquely predicted several psychosocial outcomes. Wellness-promoting psychosocial interventions may be important for this population.